-6-8(4n+8)=2(1-4n)

Simple and best practice solution for -6-8(4n+8)=2(1-4n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-8(4n+8)=2(1-4n) equation:


Simplifying
-6 + -8(4n + 8) = 2(1 + -4n)

Reorder the terms:
-6 + -8(8 + 4n) = 2(1 + -4n)
-6 + (8 * -8 + 4n * -8) = 2(1 + -4n)
-6 + (-64 + -32n) = 2(1 + -4n)

Combine like terms: -6 + -64 = -70
-70 + -32n = 2(1 + -4n)
-70 + -32n = (1 * 2 + -4n * 2)
-70 + -32n = (2 + -8n)

Solving
-70 + -32n = 2 + -8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8n' to each side of the equation.
-70 + -32n + 8n = 2 + -8n + 8n

Combine like terms: -32n + 8n = -24n
-70 + -24n = 2 + -8n + 8n

Combine like terms: -8n + 8n = 0
-70 + -24n = 2 + 0
-70 + -24n = 2

Add '70' to each side of the equation.
-70 + 70 + -24n = 2 + 70

Combine like terms: -70 + 70 = 0
0 + -24n = 2 + 70
-24n = 2 + 70

Combine like terms: 2 + 70 = 72
-24n = 72

Divide each side by '-24'.
n = -3

Simplifying
n = -3

See similar equations:

| -2x+15=20 | | 2x^4-5x^3-3x^2+x=0 | | (7+i)(6-9i)= | | a-2+5a=22 | | 11xy^6+77x^3y^4= | | -3x^2+42=0 | | 12+7b=6b | | 4.2=7Z+2.8 | | 4d-11=2b+7 | | -5-1=3x-17 | | 15x-5y=20findy | | -3.2x+31.5=65.1 | | 4x(20x)= | | 8(2-2a)+4(1-5a)=56 | | 8=2(4j+1)-5 | | 4w^2-35w+24=0 | | 3x+6+32=53 | | e^5x-6=76 | | 11y+5=-5+6y | | -2(-2f-3)=2(4f-7) | | .2+4=1.2x+8.0 | | 20x+30=4 | | 12=2(3n+1)-8(5n+3) | | 4y-9(3y-2)= | | Y=-.01x^2+.5x+3 | | 32+6x=53 | | 118-3.8t=7.36-1.9t | | (16x-6)=180 | | .26(2.39x-4.91)=10.64 | | 6x+9x+x=180 | | -2x-4(7x-2)=-6x+8 | | 0.125(6+n)=2.50 |

Equations solver categories